Dinamika Partisipasi Masyarakat Dalam Pembangunan Desa Pintareng, Sulawesi Selatan - Anisa Octaningrum; Annisa Risky Zuniati; Heny Nur Aulia; Nurdin (Indonesian Journal Publisher, 2025)
In village development, community participation is required. This research aims to further examine the level of community participation in Pintareng Village and the impact of community participation on development planning. This research uses a qualitative research method with a literature study approach. Data collection was obtained through written sources relevant to the research. The result of this research is that the low level of participation in Pintareng Village is evident from the lack of contribution of ideas and physical involvement of the community in the development process. The community is not fully aware of the importance of their role in planning and implementing development programs, which causes them to be less actively involved. Low community participation negatively impacts the gap between local needs and government policies, leading to irrelevant projects, lack of social support, and low quality of development. To address this, village governments need to improve socialization, facilitate inclusive deliberations, and provide incentives to active citizens, so that development is more in line with community needs and sustainable.